Effect of high levels of zinc on antibody response and total white blood cell in broiler chicks vaccinated against coccidiosis - S. A. Sajadifar (ՀՀ ԳԱԱ հրատ.)
In this study one-day-old broiler chicks were used with three dietary zinc (40, 120 and 200 mg/kg). At 2, 22, 32, 42 days of age, the blood serums were tested for antibody titer against Newcastle disease vaccination (NDV), using the standard Haemagglutination Inhibition (HI) test. Ցինկի 120 և 200 մգ/կգ չափաբաշիններով բրոյլեր ճտերին կերակրման դեպքում 42-րդ օրը նկատվել է նյուքասլյան հիվանդության նկատմամբ վակցինացիոն հակամարմինների տիտրի բարձրացում և արյան մեջ լեյկոցիտների ընդհանուր քանակության ավելացում: Нашими исследованиями установлено, что скармливание цыплятам цинка в дозах 120 и 200 мг/кг приводит к значительному повышению титра вакцинационных антител против болезни Ньюкасла и общему количеству лейкоцитов в крови на 42-й день.
Keywords: Biology; Immunology; Epidemiology